2005
DOI: 10.3200/aeoh.60.5.249-256
|View full text |Cite
|
Sign up to set email alerts
|

Personal Use of Hair Dyes and Hematolymphopoietic Malignancies

Abstract: In the context of a population-based case-control study in Italy, the authors investigated the possible association between the personal use of hair dyes and non-Hodgkin's lymphoma (NHL), leukemia, multiple myeloma, and Hodgkin's disease. They collected all incident cases of hematolymphopoietic malignancies; the control group was formed with a random sample of the general population. Overall, the authors interviewed 2,737 research subjects and 1,779 control subjects. Among women, the authors found no associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…This population-based case–control study showed no association between use of hair colouring products and risk of multiple myeloma. Our study is consistent with null associations reported in three case–control studies7 8 15 and two cohort studies 6 16. Two case–control studies and one cohort study, however, have reported hair colour use as a risk factor for myeloma especially among those reporting use of dark hair dyes for long periods of time5 9 14; we did not observe this association here.…”
Section: Discussionsupporting
confidence: 92%
“…This population-based case–control study showed no association between use of hair colouring products and risk of multiple myeloma. Our study is consistent with null associations reported in three case–control studies7 8 15 and two cohort studies 6 16. Two case–control studies and one cohort study, however, have reported hair colour use as a risk factor for myeloma especially among those reporting use of dark hair dyes for long periods of time5 9 14; we did not observe this association here.…”
Section: Discussionsupporting
confidence: 92%
“…Intriguingly, some chemical agents, such as pesticides, herbicides, hair dyes, or environmental tobacco and physical exposure, such as magnetic field radiation, have also been reported as associated with increased risk of CLL. 5,[16][17][18][19][20][21] These correlations provide the rational that the birth-cohort effect found in Taiwanese might be a consequence of environmental influences from the westernization of lifestyle. We also extracted the CLL incidence data from SEER for Asian/Pacific Islanders who are ethnically closer to Taiwanese but have been exposed to the westernized lifestyle.…”
Section: Discussionmentioning
confidence: 80%
“…Although various government and private agencies are taking every effort to limit lead and other metal toxicities, through meticulous legislation and public awareness, lead poisoning is still considered to be a major health problem from many non-occupational sources, mainly drinking water, traditional medicine, food supplements, cosmetics and toys [14][15][16][17][18][19][20][21]. Unfortunately, hazardous traditional therapies, food supplement, cosmetics and toys are sold widely without any adequate safety studies, licensing or warning.…”
Section: Discussionmentioning
confidence: 99%